2010
DOI: 10.1177/1352458510379819
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception in natalizumab-treated multiple sclerosis patients and their neurologists

Abstract: Patients had a significantly worse perception of multiple sclerosis as a malignant disease. We conclude that patients were willing to accept a higher risk of PML than neurologists. Coherent with their perception of risks and benefits, patients were also more willing to continue treatment. Open information about treatment-related risks is appreciated and might support shared decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 19 publications
2
66
1
1
Order By: Relevance
“…The comparison between the answers profile for this population and two previously published cohorts with similar methodology 12,13 , revealed that our patients perceive MS severity and the risks associated with natalizumab similarly, but their RAS is lower than for patients from these two European cohorts (Table 4 and the Figure).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison between the answers profile for this population and two previously published cohorts with similar methodology 12,13 , revealed that our patients perceive MS severity and the risks associated with natalizumab similarly, but their RAS is lower than for patients from these two European cohorts (Table 4 and the Figure).…”
Section: Resultsmentioning
confidence: 99%
“…Our study was modeled after Tur's work 13 , which is a little different from Heesen's study 12 , restricting direct comparison of this cohort to the German patients. Furthermore, we evaluated a young patient population with a mean disease duration of only nine years, with low-to-moderate disability and with most of them having received only one or two disease modifying drugs.…”
Section: Fox Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Although most patients seem to be willing to receive high doses of vitamin D (even megadoses, without any scientific evidence for their use), not too many patients seem to be willing to stop smoking, drinking, starting with exercise and weight loss programs. In fact, there are reports clearly showing that patients are willing to run the risk of lifeendangering side effects from immunosuppressive drugs for MS in order to continue with the treatment 57,58 . Furthermore, thousands of patients with MS worldwide were found to be willing to submit themselves to a vascular surgical procedure to treat their MS for which there was no scientific basis 59 .…”
Section: Discussionmentioning
confidence: 99%
“…112,113 Hence, it is not surprising that patients might be more willing to accept SAEs in return for a reduced risk of disability progression than physicians. 114 Given these differences in treatment perspectives between patients and physicians, neurologists should strongly encourage their patients to formulate their own values and preferences regarding their medical care. 115 In addition, healthcare providers have a duty to ensure patients understand the complex information given to them.…”
Section: How To Integrate the Patient's Treatment Expectations Into Imentioning
confidence: 99%